An Analysis of Head Impact angle on the Dynamic Response of a Hybrid III Headform and Brain Tissue Deformation - Oeur, Anna (Université d'Ottawa / University of Ottawa, 2012)
The objective of this research was to better understand how impact angle influences headform dynamic response and brain tissue deformation. A bare headform was impacted using a pneumatic linear impactor at 5.5 m/s. The impacts were directed on the front and side location at angles of 0, 5, 10 and 15° rightward rotations as well as -5, -10 and -15° (leftward) rotations at the side to examine the characteristics of the head and neckform on the results. Peak resultant linear and rotational accelerations from the headform as well as peak maximum principal strain (MPS) and von Mises stress (VMS) estimated from a brain finite element model were used to measure the effect of impact angle. Significant results were dependent upon the impact angle and location as well as the dependent variable used for comparison (p <0.05). Impact angle produced significant differences in rotational acceleration and MPS at both the front and side; however angle only had an effect on VMS and linear acceleration at the front and side locations, respectively. These findings show that the effect of impact angle is asymmetrical and is specific to the dependent variable. This study suggests that varying impact angle alone may not be as influential on headform dynamic response and brain tissue deformation and that the severity of an impact may be more of a function of how both location and angle create high risk conditions.
Keywords: head impact; impact angle; Hybrid III; finite element analysis